Inflammation-Related Genes Serve as Prognostic Biomarkers and Involve in Immunosuppressive Microenvironment to Promote Gastric Cancer Progression - Wei, Yuanfeng; Gao, Limin; Yang, Xi; Xiang, Xiaoyu; Yi, Cheng (Frontiers in Medicine, 2022)
Gastric cancer (GC) is a typical inflammatory-related malignant tumor which closely related to helicobacter pylori infection. Tumor inflammatory microenvironment plays a crucial role in tumor progression and affect the clinical benefit from immunotherapy. In recent years, immunotherapy for gastric cancer has achieved promising outcomes, but not all patients can benefit from immunotherapy due to tumor heterogeneity. In our study, we identified 29 differentially expressed and prognostic inflammation-related genes in GC and normal samples. Based on those genes, we constructed a prognostic model using LASSO algorithm, which categorized GC patients into two groups. The high-risk group have the characteristics of “cold tumor” and have a poorer prognosis. In contrast, low-risk group was “hot tumor” and had better prognosis. Targeting inflammatory-related genes and remodeling tumor microenvironment to turn “cold tumor” into “hot tumor” may be a promising solution to improve the efficacy of immunotherapy for GC patients.